Aplicação do sistema PTAL na avaliação da acessibilidade ao transporte público em cidade de médio porte - Martinez, Manuel Ricardo Galileo Ramires (2016)
For several years, Public Transportation Accessibility has been understood within the laws of each country, as a right that allows equality of opportunity through of the access of all people to the services and spaces of the city. Just, only in recent decades, cities began to make the evaluation of their public transport system and the level of accessibility give to the public. These analyses emerged due to worldwide increase of the number of vehicles, which have caused problems in different kinds of cities: congestion on roads, increase of air pollution, including a great contribution to global warming. One of the policies, which currently seeks to counter these difficulties, is to encourage public transport systems above the use of private cars. That is why it began to appear new studies trying to identify the problems faced by the transport system in the cities and the preference of the private vehicle use, finding that comfort and the level of access, have a direct link with the choice of transport. Therefore, the government of the city of London, created a system known as assessment PTAL, which measures the level of accessibility to public transport through regional indicators that are involved with both the system infrastructure of the transport and the city, as with the present social activities in the regions. In this context, the present study aims to evaluate the accessibility of public transport in the city of Passo Fundo, Rio Grande do Sul, Brazil, based on the methodology of PTAL indicators assessment system, with the implementation of geographic information system (GIS) software. It analyzes regionally the city and identify the shortcomings of the current system of public transportation, taking into account an assessment of the city’s existing infrastructure and the population demand. For the information required in this research were related data of government bodies and extracted data from space-time information programs such as Google Earth. Among the partial results, it found an important difference between the amount of the necessary stops and the actual number that now has the city, leading to a possible reduction in system efficiency and higher consumption of economic and environmental resources.